ON 2D P COLONIES AND GREY WOLF ALGORITHM - Valenta, Daniel; Langer, Miroslav (International Multidisciplinary Scientific GeoConference SGEM, 2020)
P colonies (see [2]) are a well-established version of the P systems (see [3]), the computational device based on membrane computing. One branch of the research of the P-colonies focuses on the possibility to consider the two-dimensional environment, in which the agents act, and the 2D P colonies (see [1]) were introduced. 2D P colonies showed to be suitable for the simulations of various (not only) multi-agent systems, and natural phenomena, like the flash floods. The Grey wolf algorithm (see [4]) is the optimization-based algorithm inspired by social dynamics found in packs of grey wolves and by their ability to create dynamically hierarchies in which every member has a clearly defined role. The wolves' primary goal is to find and hunt down prey, which in our case equals finding the optimal solution to the given problem. The grey wolf algorithm displays positive results thanks to the principles of randomness and communication between wolves. In this paper, we propose a model of the 2D P colonies with the blackboard. The only communicating device in the case of the 2D P colony is the environment, what is not sufficient for some kinds of multi-agent systems. The blackboard is a communication device accessible for all the agents at the same time, and it allows to share all the necessary information. An agent can read and write on the blackboard using its communicating rules. Using the blackboard allows us to simulate the grey wolf algorithm using the 2D P colony, describe and formalize the behavior of the wolves and agents in the multi-agent system in general.